Andrey Bely : Spirit of Symbolism. - Malmstad, John E. (Studies of the Harriman Institute., 2019)
No figure in turn-of-the-century Russia, John Malmstad asserts, better epitomizes the paradoxes of that era than Andrey Bely (1880-1934). Eulogized by Boris Pasternak as "the most remarkable writer of our age" and now widely regarded as the seminal figure in Russian modernism and as one of the major writers of this century, Bely subjected the received standards of truth and value in literature to a penetrating and radical critique. After a long period of suppression under the Stalinist regime, Bely has become the object of growing critical attention in both East and West. Originating in a symposium held in 1984 under the auspices of the Harriman Institute at Columbia University on the fiftieth anniversary of Bely's death, this volume includes ten essays by established scholars of modern Russian literature, including leading Western specialists on Bely. The essays survey Bely's major works in all genres, summarize present research on Bely, reassess critical approaches, and offer fresh interpretations. Analytic summaries of primary works make the essays fully accessible to non-Slavist readers.